Tuning the Structure, dimensionality and Luminescent properties of Lanthanide Metal-Organic Frameworks under Ancillary Ligand Influence - D'Vries, Richard Fernando (2016)
This manuscript addresses the synthesis, structural characterization and optical properties of a 1D coordination polymer (CPs) and 2D and 3D Metal–Organic Frameworks (MOFs) obtained from lanthanide metals, 3-hydroxinaftalene-2,7-disulfonic acid (3-OHNDS) and two different phenanthroline derivates as ancillary ligands. The first is a family of 2D compounds with formula [Ln(3-OHNDS)(H2O)2], where Ln = La(1), Pr(2), Nd(3) and Sm(4). The addition of 1,10-phenanthroline (phen) in the reaction produces 1D compounds with general formula [Ln(3-OHNDS)(phen)(H2O)]·3H2O, where Ln = La(5), Pr(6), Nd(7) and Sm(8). Finally, the synthesis with 3,4,7,8-tetramethyl-1,10-phenanthroline (3,4,7,8-TMPhen) as an ancillary ligand results in the formation of the 3D [La(3-OHNDS)(3,4,7,8-TMphen)(H2O)] (9) compound. The photoluminescence (PL) properties of 1D and 2D compounds were fully investigated in comparison with the 3-OHNDS ligand. One of the most important results was the obtaining of a white-light single-emitter without adding dopant atoms in the structure. With all these results in mind it was possible to establish structure–property relationships.